Catheter Ablation of Nonparoxysmal Atrial Fibrillation Using Electrophysiologically Guided Substrate Modification During Sinus Rhythm After Pulmonary Vein Isolation. (February 2016) - Yang, Gang; Yang, Bing; Wei, Youquan; Zhang, Fengxiang; Ju, Weizhu; Chen, Hongwu; Li, Mingfang; Gu, Kai; Lin, Yazhou; Wang, Benqi; Cao, Kejiang; Kojodjojo, Pipin; et al.
Abstract : Background—: The high incidence of postprocedural atrial tachycardia reduces the absolute arrhythmia-free success rate of extensive ablation strategies to treat nonparoxysmal atrial fibrillation (NPAF). We hypothesized that a strategy of targeting low-voltage zones and sites with abnormal electrograms during sinus rhythm (SR-AEs) in the left atrium after circumferential pulmonary vein isolation and cavotricuspid isthmus ablation in patients with NPAF is superior. Methods and Results—: A total of 86 consecutive patients with NPAF were enrolled in study group. After circumferential pulmonary vein isolation, cavotricuspid isthmus ablation and cardioversion to SR, high-density mapping of left atrium was performed. Areas with low-voltage zone and SR-AE were targeted for further homogenization and elimination, respectively; 78 consecutive sex- and age-matched patients with NPAF who were treated with the stepwise approach served as the historical control group. In the study group, 92% (79/86) were successfully cardioverted after circumferential pulmonary vein isolation and cavotricuspid isthmus ablation. Among the patients converted to SR, 70% (55/79) had low-voltage zone and SR-AE and received additional ablation, whereas in 30% (24/79) without SR-AE or low-voltage zone, no further ablation was performed. During a follow-up period of >30 months, the Kaplan–Meier estimated probability to maintain SR at 24 months was 69.8% versus 51.3%. And after a single procedure, 3.5% (3/86) developed postprocedural atrial tachycardia in study group, compared with 30% (24/78) in control group ( P =0.0003). Conclusions—: A strategy of selective electrophysiologically guided atrial substrate modification in SR after circumferential pulmonary vein isolation and cavotricuspid isthmus ablation is clinically more effective than the stepwise approach for NPAF ablation. Clinical Trial Registration—: URL:http://clinicaltrials.gov . Unique identifier: NCT01716143. Abstract : Supplemental Digital Content is available in the text.